INDENTIFIKASI PERMASALAHAN TERKAIT PENGOBATAN PADA PASIEN DISLIPIDEMIA KOMORBID DIABETES MELITUS DENGAN TERAPI STATIN DI SALAH SATU RUMAH SAKIT KOTA BANDUNG TAHUN 2023 - Rahayu, Siti Nurhaliza Nadya; Simanjuntak, Nela (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2024)
ABSTRACT Dyslipidemia and type II diabetes mellitus (DM) can occur simultaneously and can mutually worsen the patient's condition. The complexity of treatment in patients with such comorbidities potentially increases the risk of treatment-related problems. This study aims to determine the demographics of patients with type II DM comorbid dyslipidemia in one of the hospitals in Bandung City in 2023 and describe the incidence of treatment problems. This descriptive study reviewed 92 patient medical records that met the research criteria. The classification method for identifying problems related to treatment refers to Basger et al. 2015. The results showed that patients with type II DM comorbid dyslipidemia on statin therapy were dominated by women (55.43%) and elderly (59.78%). The most frequent incidence of treatment-related problems was in the subcategory of inappropriate drug combinations. There were 78 cases resulting in increased therapeutic effect and the most common was related to the prescription of lansoprazole with atorvastatin; 55 cases of interactions resulting in reduced therapeutic effect, of which the most common was related to the prescription of clopidogrel with atorvastatin. There were 4 cases that resulted in hypersensitivity reactions involving allopurinol and antihypertensive drugs. It can be concluded that clinical pharmacists intervene in reviewing patient care by considering the risks and benefits of such a combination for the patient.